Sun Protection Behavior in Danish Outdoor Workers Following a Multicomponent Intervention - Jakobsen, Marie Munk; Mortensen, Ole Steen; Grandahl, Kasper (Frontiers in Public Health, 2022)
Background: Outdoor workers can be exposed to relatively high levels of ultraviolet radiation and are at risk of developing occupational skin cancer. Implementing the use of sun protection in outdoor workers at work is therefore important. The objective of this follow-up study was to evaluate the effect of a multi-component intervention to improve the use of sun protection in Danish outdoor workers. Method: 237 Danish outdoor workers were asked to complete surveys in 2016/17 and in 2020. Multi-component intervention, between surveys, included education on skin cancer risk and use of sun protection, personal dosimetry and skin examination for signs of photodamage and skin cancer. Survey items on awareness of occupational skin cancer risk and perceived importance of sun protection as well as availability and use of sun protection at work were compared and analyzed in relation to the multi-component intervention. Results: Overall the use of sun protection at work increased significantly (composite score 4.0 in 2016/17 and 4.6 in 2020, p< 0.001). Sunscreen was by far the biggest contributor, and the only type of sun protection used at work, which changed significantly (often/always use 37% in 2016/17 and 52% in 2020, p< 0.001). The biggest influence on the increased use of sun protection at work seemed to be a significant increase in the awareness of occupational skin cancer risk (moderate/high 43% in 2016/17 and 63% in 2020, p<0.001) and perceived importance of sun protection at work (moderate/high 69% in 2016/17 and 83% in 2020, p<0.001). Conclusion: The results of this study show the potential to improve the awareness of occupational skin cancer risk as well as the perceived importance and use of sun protection at work in Danish outdoor workers by way of multi-component intervention.